INTERRELACIONES DE POLINIZACION EN ZONAS ARIDAS DE CHILE - Toro, H.; Chiappa, E.; Covarrubias, R.; Villaseñor, R. (Acta Entomológica Chilena, 2022)
This study reports the pollination ecology of Prosopis tamarugo and its relations with other species of plants growing in the salty desert of northem Chile (P. flexuosa, P. alba, P. strombulifera, P. burkartii and Caesalpinia aphylla). The following species of insects are considered the most important pollinatois: Centris mixta, C. moldenkei, Pachodynerus peruensis and the lycaenid Leptotes trigemmatus. Observations were made on the behaviour of the pollinators, inflorescence characters, fruit production and mechanisms to avoid competition.